Antropomorfism Ilahi dalam Kejadian 6:7 : Kajian Eksegetis ”Allah Menyesal” dalam Perspektif Teologi Perjanjian Lama - Margareta Margareta; Helsa Riang Tulak; Ayunita Pakiding (Damai : Jurnal Pendidikan Agama Kristen dan Filsafat, 2026)
The expression “God regretted” in Genesis 6:7 is one of the most theologically problematic statements in the Old Testament, as it seems to contradict the classical doctrine of God’s immutability. This study aims to examine the meaning of this expression through an exegetical approach, emphasizing the analysis of the Hebrew text and the lexical use of the word nāḥam. The method employed is qualitative-descriptive with a historical-grammatical and biblical-theological approach. The primary data are derived from the Hebrew text in the Biblia Hebraica Stuttgartensia and supported by lexical sources. The results indicate that the word nāḥam in Genesis 6:7 does not imply regret in the sense of wrongdoing, but rather refers to divine sorrow over the moral corruption of humanity. The expression represents a form of anthropomorphism used to depict the relationship between God and humans in language comprehensible to human beings. From an Old Testament theological perspective, this text affirms that God is relational and active in history, without compromising the consistency of His character. Therefore, the “regret of God” does not contradict the doctrine of divine immutability, but rather enriches the understanding of His involvement in human life.